Fast and controllable synthesis of AB-stacked bilayer MoS2 for photoelectric detection. (24th November 2021) - Wang, Shuang; Zhang, Yanhui; Zhao, Dongyang; Li, Jing; Kang, He; Zhao, Sunwen; Jin, Tingting; Zhang, Jiaxiang; Xue, Zhongying; Wang, Ying; Sui, Yanping; Chen, Zhiying; et al.
Abstract: In recent years, researchers have explored the interlayer stacking structure of the bilayer (BL) transition metal dichalcogenides (TMDCs) and found that it has unique impact on the electrical, optical, and vibrational properties of TMDCs. Unfortunately, the size of BL TMDCs synthesized by the pre-existing methods is not large. In addition, there is not any effective mean to control the number of layers as well as the stack structure. This is the major limiting factor for further exploration of the properties of BL TMDCs. We report a new method for the rapid and controllable growth of AB-stacked BL MoS2 . Firstly, the mixed solution of Na2 MoO4 and NaOH was spun on the sapphire substrate and then sulfurated. The BL MoS2 of AB-stacked can be obtained by changing the time of sulfur introduction. The size of the BL MoS2 is related to the parameters of sulfur. The maximum size of BL MoS2 grown by this method can reach 288 μ m, and the average size can reach about 200 μ m, which is larger than the size reported in most articles. In addition, the growth rate of BL MoS2 can be clearly increased by the spin-coating growth method and the fastest growth rate is up to 144 μ m min −1, which is far higher than other published reports at present. Subsequently, a photodetector based on BL MoS2 was prepared. The response time of rising edge is about 0.32 ms, and that of falling edge is about 3.2 ms. The detector prepared by us shows excellent photoelectric detection performance. Therefore, the excellent performance of BL MoS2 makes it have a broad application prospect in the field of high-performance electronics and optoelectronics.